The link between immunity and hypertension in the kidney and heart - Benson, Lance N.; Guo, Yunping; Deck, Katherine; Mora, Christoph; Liu, Yunmeng; Mu, Shengyu (Frontiers in Cardiovascular Medicine, 2023)
Hypertension is the primary cause of cardiovascular disease, which is a leading killer worldwide. Despite the prevalence of this non-communicable disease, still between 90% and 95% of cases are of unknown or multivariate cause (“essential hypertension”). Current therapeutic options focus primarily on lowering blood pressure through decreasing peripheral resistance or reducing fluid volume, but fewer than half of hypertensive patients can reach blood pressure control. Hence, identifying unknown mechanisms causing essential hypertension and designing new treatment accordingly are critically needed for improving public health. In recent years, the immune system has been increasingly implicated in contributing to a plethora of cardiovascular diseases. Many studies have demonstrated the critical role of the immune system in the pathogenesis of hypertension, particularly through pro-inflammatory mechanisms within the kidney and heart, which, eventually, drive a myriad of renal and cardiovascular diseases. However, the precise mechanisms and potential therapeutic targets remain largely unknown. Therefore, identifying which immune players are contributing to local inflammation and characterizing pro-inflammatory molecules and mechanisms involved will provide promising new therapeutic targets that could lower blood pressure and prevent progression from hypertension into renal or cardiac dysfunction.